Synthesis, characterization and electrochemical properties of novel metal free and zinc(II) phthalocyanines of ball and clamshell types - ÖZKAYA, ALİ RIZA (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The phthalodinitrile derivative I was prepared by the reaction of 4-nitrophthalonitrile and 1,3-dimethoxy-4-tert-butylcalix[4]arene in dry dimethylsulfoxide as the solvent, in the presence of the base K2CO3, by nucleophilic substitution of an activated nitro group in an aromatic ring. The tetramerization of compound I gave a binuclear zinc(II) phthalocyanine and a metal-free phthalocyanine of the ball type, 2 and 3, respectively. Its condensation with 4,5-bis(hexylthio)phthalonitrile results in a binuclear plithalocyanine of the clamshell type, 4. The newly synthesized compounds were characterized by elemental analysis, UV-Vis, IR, MS and H-1 NMR spectra. The electronic spectra exhibit an intense pi -> pi* transition with characteristic Q and B bands of the phthalocyanine core. The electrochemical properties of 2-4 were examined by cyclic voltammetry in non-aqueous media. The voltammetric results showed that while there is no considerable interaction between the two phthalocyanine rings in 4, the splitting of a molecular orbital occurs as a result of the strong interaction between the phthalocyanine rings in 2 and 3. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: phthalocyanine; ball-type; clamshell; calixarenes; tetramerization; electrochemistry; GAS-SENSING PROPERTIES; SPECTROSCOPY; DERIVATIVES; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; SPECTROELECTROCHEMISTRY; AGGREGATION; CHEMISTRY; DESIGN; CELLS